Discerning dominant temporal patterns of bio-optical properties in the northwestern Mediterranean Sea (BOUSSOLE site) - Bellacicco, M.; Vellucci, V.; D'Ortenzio, F.; Antoine, David (PERGAMON-ELSEVIER SCIENCE LTD, 2019)
© 2019 A wavelet analysis has been applied, for the first time, to 3-year high-frequency field observations of bio-optical properties (i.e. chlorophyll-fluorescence, beam attenuation and backscattering coefficients) in the northwestern Mediterranean Sea (BOUSSOLE site), in order to identify their dominant temporal patterns and evolution. A cross-wavelet and coherence analysis has also been applied to paired bio-optical coefficients time-series at the BOUSSOLE site, which allows identifying the temporal relationship between the cycles of the bio-optical properties. Annual, six- and four-month, intra-seasonal (i.e., mid- and short-terms) cycles are identified from the time-series analysis. The periodicities of chlorophyll-fluorescence, beam attenuation and particulate backscattering coefficients correlate well at different temporal scales and specific seasons. At annual, six- and four-month scales, different bio-optical properties follow rather similar patterns, likely driven by physical forcing. Intra-seasonal variability consists in both mid- and short-term variations. The former dominates during the winter and are related to episodic bloom events, while the latter variations (i.e., diel) prevail during summer, in a stratified water column.